Perancangan Desain Kemasan Produk Manisan Buah Umkm Sola Gracia untuk Membangun Citra Merek - Stevanie Yuliana; Ayyub Anshari Sukmaraga (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2019)
Packaging has become one of the main points of the buying and selling process today, so that with attractive and easily found packaging by the community, it is expected that sales will increase. Sola Gracia is a Small and Medium Business that is struggling to increase sales through sales targeting consumers aged 25 to 40 years. But there is still a need for improvements in existing packaging designs. The design will be focused on the introduction of products with attractive packaging so that consumers will be interested in buying these products. Besides that design also includes marketing through social media so that consumers will get products easily. The method used is research and development, and questionnaires. The results of these methods will help to design packaging that is in accordance with the consumers wishes. Furthermore, to test the packaging design, trial packaging was made. It is known that consumers prefer appetizing and colorful packaging. The result that was already fixed on packaging will be validated using online questionnaires. This stage is used to depict how people accept the packaging.